Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Sure! Let's find the limit:
[tex]\[ \lim_{{x \to 1}} \frac{x^2 + 1}{x^2 - 3x + 2} \][/tex]
### Step 1: Substitute [tex]\(x = 1\)[/tex]
First, we should substitute [tex]\(x = 1\)[/tex] into the expression to see if it yields a determinate form:
[tex]\[ \frac{1^2 + 1}{1^2 - 3(1) + 2} = \frac{1 + 1}{1 - 3 + 2} = \frac{2}{0} \][/tex]
Since the denominator becomes 0, the expression is undefined at [tex]\( x = 1 \)[/tex]. Hence, we must find the limit using other methods, since directly substituting gives an indeterminate form of [tex]\(\frac{2}{0}\)[/tex].
### Step 2: Factor the Denominator
Factor the denominator [tex]\(x^2 - 3x + 2\)[/tex]:
[tex]\[ x^2 - 3x + 2 = (x - 1)(x - 2) \][/tex]
Now rewrite the original function with the factored form:
[tex]\[ \frac{x^2 + 1}{x^2 - 3x + 2} = \frac{x^2 + 1}{(x - 1)(x - 2)} \][/tex]
### Step 3: Analyze the Behavior Around [tex]\( x = 1 \)[/tex]
Since the denominator becomes zero at [tex]\( x = 1 \)[/tex], let's analyze the behavior of the function as [tex]\( x \)[/tex] approaches 1 from the left ([tex]\( x \to 1^- \)[/tex]) and from the right ([tex]\( x \to 1^+ \)[/tex]).
#### As [tex]\( x \to 1^- \)[/tex]:
- Numerator: [tex]\( x^2 + 1 \to 1 + 1 = 2 \)[/tex]
- Denominator: [tex]\( (x - 1)(x - 2) \)[/tex] where [tex]\( x - 1 \)[/tex] approaches 0 but is slightly negative (since [tex]\( x < 1 \)[/tex]), and [tex]\( x - 2 \)[/tex] is negative when [tex]\( x < 1 \)[/tex].
So, [tex]\((x - 1)(x - 2)\)[/tex] will be positive but very close to 0.
Thus, [tex]\( \frac{2}{(x - 1)(x - 2)} \to \frac{2}{+0} \)[/tex] which indicates [tex]\( +\infty \)[/tex].
#### As [tex]\( x \to 1^+ \)[/tex]:
- Numerator: [tex]\( x^2 + 1 \to 1 + 1 = 2 \)[/tex]
- Denominator: [tex]\( (x - 1)(x - 2) \)[/tex] where [tex]\( x - 1 \)[/tex] approaches 0 but is slightly positive (since [tex]\( x > 1 \)[/tex]), and [tex]\( x - 2 \)[/tex] is negative when [tex]\( x < 2 \)[/tex].
So, [tex]\((x - 1)(x - 2)\)[/tex] will be negative but very close to 0.
Thus, [tex]\( \frac{2}{(x - 1)(x - 2)} \to \frac{2}{-0} \)[/tex] which indicates [tex]\( -\infty \)[/tex].
### Conclusion:
Since as [tex]\( x \)[/tex] approaches 1 from the left, the function approaches [tex]\( +\infty \)[/tex], and as [tex]\( x \)[/tex] approaches 1 from the right, the function approaches [tex]\( -\infty \)[/tex], the overall limit does not exist in the standard sense. However, in one-sided limits, and for certain conventions, it can be summarized as:
[tex]\[ \lim_{{x \to 1}} \frac{x^2 + 1}{x^2 - 3x + 2} = -\infty \][/tex]
Thus, the given limit evaluates to:
[tex]\[ \boxed{-\infty} \][/tex]
[tex]\[ \lim_{{x \to 1}} \frac{x^2 + 1}{x^2 - 3x + 2} \][/tex]
### Step 1: Substitute [tex]\(x = 1\)[/tex]
First, we should substitute [tex]\(x = 1\)[/tex] into the expression to see if it yields a determinate form:
[tex]\[ \frac{1^2 + 1}{1^2 - 3(1) + 2} = \frac{1 + 1}{1 - 3 + 2} = \frac{2}{0} \][/tex]
Since the denominator becomes 0, the expression is undefined at [tex]\( x = 1 \)[/tex]. Hence, we must find the limit using other methods, since directly substituting gives an indeterminate form of [tex]\(\frac{2}{0}\)[/tex].
### Step 2: Factor the Denominator
Factor the denominator [tex]\(x^2 - 3x + 2\)[/tex]:
[tex]\[ x^2 - 3x + 2 = (x - 1)(x - 2) \][/tex]
Now rewrite the original function with the factored form:
[tex]\[ \frac{x^2 + 1}{x^2 - 3x + 2} = \frac{x^2 + 1}{(x - 1)(x - 2)} \][/tex]
### Step 3: Analyze the Behavior Around [tex]\( x = 1 \)[/tex]
Since the denominator becomes zero at [tex]\( x = 1 \)[/tex], let's analyze the behavior of the function as [tex]\( x \)[/tex] approaches 1 from the left ([tex]\( x \to 1^- \)[/tex]) and from the right ([tex]\( x \to 1^+ \)[/tex]).
#### As [tex]\( x \to 1^- \)[/tex]:
- Numerator: [tex]\( x^2 + 1 \to 1 + 1 = 2 \)[/tex]
- Denominator: [tex]\( (x - 1)(x - 2) \)[/tex] where [tex]\( x - 1 \)[/tex] approaches 0 but is slightly negative (since [tex]\( x < 1 \)[/tex]), and [tex]\( x - 2 \)[/tex] is negative when [tex]\( x < 1 \)[/tex].
So, [tex]\((x - 1)(x - 2)\)[/tex] will be positive but very close to 0.
Thus, [tex]\( \frac{2}{(x - 1)(x - 2)} \to \frac{2}{+0} \)[/tex] which indicates [tex]\( +\infty \)[/tex].
#### As [tex]\( x \to 1^+ \)[/tex]:
- Numerator: [tex]\( x^2 + 1 \to 1 + 1 = 2 \)[/tex]
- Denominator: [tex]\( (x - 1)(x - 2) \)[/tex] where [tex]\( x - 1 \)[/tex] approaches 0 but is slightly positive (since [tex]\( x > 1 \)[/tex]), and [tex]\( x - 2 \)[/tex] is negative when [tex]\( x < 2 \)[/tex].
So, [tex]\((x - 1)(x - 2)\)[/tex] will be negative but very close to 0.
Thus, [tex]\( \frac{2}{(x - 1)(x - 2)} \to \frac{2}{-0} \)[/tex] which indicates [tex]\( -\infty \)[/tex].
### Conclusion:
Since as [tex]\( x \)[/tex] approaches 1 from the left, the function approaches [tex]\( +\infty \)[/tex], and as [tex]\( x \)[/tex] approaches 1 from the right, the function approaches [tex]\( -\infty \)[/tex], the overall limit does not exist in the standard sense. However, in one-sided limits, and for certain conventions, it can be summarized as:
[tex]\[ \lim_{{x \to 1}} \frac{x^2 + 1}{x^2 - 3x + 2} = -\infty \][/tex]
Thus, the given limit evaluates to:
[tex]\[ \boxed{-\infty} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.